Theoretical Characterization of Germanene Doped with Main Group Elements - Denis, Pablo A.; Laranjeira, Jose A. S. [UNESP]; Sambrano, Julio R. [UNESP] (Wiley, 2024)
Herein, using density functional calculations, we studied the substitutional doping in germanene with B, C, N, O, Al, Si, P, S, Ga, As, and Se. Nitrogen is the element that can be more easily incorporated into the germanene lattice, followed by silicon, carbon, and boron. Almost all dopants were efficient in opening a band-gap. Yet, caution should be taken because this opening strongly depends on the dopant concentration. Carbon and sulfur were the most effective elements for band-gap opening. C-doping generates the lowest effective masses (me*/m0=mh*/m0=0.09). The equal me and mh values indicate an intrinsic semiconductor behavior, a characteristic shared by the chalcogenides-doped systems. Additionally, we performed a detailed analysis of the preferred disposition of dopants in the germanene lattice. In contrast with the results obtained for graphene, when multiple atoms are introduced in the germanene framework, they do not prefer to be agglomerated, adopting a random disposition, except in the case of sulfur and nitrogen, which favored specific dopant arrangement. Two sulfur dopants showed a notorious preference for replacing a Ge−Ge bond but without forming an S−S linkage, thus adopting a thiophene-like structure that may impart germanene exciting properties, as observed for S and N codoped graphene.
Keywords: density functional calculations; germanene; graphene; two-dimensional materials